Criticism of Matan and Examples of Hadith - Muhammad Fadhlurrahman; Romlah Abubakar Askar; Munzir Suparta (Penerbit Hellow Pustaka, 2025)
Matan criticism, a vital component of hadith studies, distinguishes authentic narrations by evaluating hadith content for logical coherence, Quranic consistency, and alignment with Sharia principles. This study employs a descriptive-analytical literature review to explain and illustrate matan criticism, emphasizing its necessity in preserving Islamic teachings, especially when addressing anomalous (syadz) or contradictory hadiths.